EDUKASI UNTUK MENCEGAH KEKERASAN TERHADAP ANAK-ANAK - Queen, Dhiena; Sutanto, Shienny Megawati (Jurnal VICIDI, 2021)
This scientific work focuses on the educational background of violence against children. This scientific work aims to create an educational medium to prevent violence against children in Indonesia. The importance of violence agaisnt children education is because violence agaisnt children cases are worsening and increasing every day. However, even though parental knowledge about child protection is high, it is still not sufficient to reduce violence against children cases. It takes an active role from every level of society both from the government, society itself and the mass media. To maximize their role, thorough and in-depth education is needed on violence against children. Keywords: Education, Child Abuse, Prevention